Normal psychomotor development in a child with mosaic trisomy and pericentric inversion of chromosome 9. - Frydman, M (1981)
A female infant with trisomy 9 in 58% of her cells is reported. Multiple congenital malformations were present, but she had normal psychomotor development. A pericentric inversion involving a portion of the centromeric heterochromatin of chromosome 9 was identified in the patient and her mother. This variant chromosome 9 was present in duplicate in the trisomic line. Since similar variants of 9qh have been found repeatedly in this syndrome, we feel that this association may be a non-random one.